THE EFFECT OF LRD STRATEGY ON STUDENTS’ READING COMPREHENSION VIEWED BY THEIR READING INTEREST - Dika Sakina; Annisa Astrid; Husnaini Husnaini (Universitas Lambung Mangkurat, 2026)
Reading comprehension remains a crucial skill for EFL students, yet many junior high school learners still experience difficulties in understanding texts. This study aimed to investigate the effect of the Listen-Read-Discuss (LRD) strategy and reading interest on students’ reading comprehension achievement, as well as the interaction between both variables. A factorial design was employed involving eighth-grade students of MTsN 4 Musi Banyuasin in the 2025/2026 academic year. The sample comprised control and experimental classes, and the data were collected using a reading interest questionnaire and a reading comprehension test. Both instruments were considered valid and reliable. The data were analyzed using Two-Way ANOVA in IBM SPSS Statistics version 27. The results revealed that the teaching strategy significantly affected students’ reading comprehension, with students taught using the LRD strategy achieving higher scores than those taught using the conventional strategy. Reading interest also showed a significant effect on reading comprehension achievement. However, no significant interaction was found between teaching strategy and reading interest. These findings indicate that the LRD strategy improves students’ reading comprehension regardless of their reading interest levels and can be considered an effective alternative in EFL reading instruction.